Pengaruh Employee Engagement Terhadap Organizational Citizenship Behavior (OCB) Dan Kinerja Karyawan Pada Bank Mandiri KCP Mandiri Universitas Jember - Harsono, Nagest Dwi; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
This study aims to determine the implementation of OCB in increasing employee engagement on the performance of Bank Mandiri KCP Mandiri University of Jember employees. The population in this study were all employees of Bank Mandiri KCP Mandiri University of Jember, totaling 30 employees. In taking the sample, the Saturated Sample method/Census Method is applied, which is a technique for determining a sample where all members of the population are selected as samples. The reason for using this method is because the total number of employees of Bank Mandiri KCP Mandiri University of Jember as a whole is 30 employees. The data analysis method used in this research is path analysis. The results showed that employee engagement had an effect on the OCB of Bank Mandiri KCP Mandiri University of Jember employees. Employee engagement affects the performance of PNM Probolinggo Branch employees. OCB affects the performance of Bank Mandiri KCP Mandiri University of Jember employees